Reliable and Clinically Significant Change in Outcomes for Forensic Mental Health Inpatients: Use of the HoNOS-Secure. Issue 2 (3rd April 2017) - Dickens, Geoffrey L.; O'Shea, Laura E.
ABSTRACT: Outcomes measures are commonly derived from post-discharge recidivism, readmission, and mortality rates but information about common outcomes across admission is scant. We determined whether reliable and clinically significant change in risk-related need, behavior, functioning, and symptoms occurred during admission by analysing routinely collected HoNOS-secure data ( N = 418). We calculated between-group differences in baseline scores and rates of change, the proportion of patients for whom change was reliable, and, of those, the proportion whose scores fell by a clinically significant margin. Reliable change was demonstrated for 4.8% and 5.7% of patients on the HoNOS-secure scale and security scale respectively, and that change was rarely clinically significant. In a context in which services rarely report on routinely collected data for a range of outcomes, we found that HoNOS-secure captured little of any clinical change that may have occurred. Further research should determine whether the HoNOS-secure is a suitable tool for routine outcomes reporting.